Varenicline Nasal Spray for the Treatment of Dry Eye Disease Following Corneal Collagen Crosslinking - Tanner J. Ferguson; David Durgan; Travis Whitt; Russell J. Swan (Ophthalmology and Therapy)
Abstract Introduction To evaluate the safety and effectiveness of a varenicline solution nasal spray 0.03 mg (VNS) in reducing signs and symptoms of dry eye disease following corneal collagen cross-linking (CXL). Methods Subjects undergoing CXL were randomized to VNS (study) or vehicle (control) twice daily and initiated treatment with VNS 28 days prior to the procedure with continued use for 28 days following the procedure. After starting treatment, subjects were seen on the day of surgery and postoperatively at days 2, 3, 4, 7 and 28. The primary outcome measure was the change in the National Eye Institute Visual Function Questionnaire (NEI-VFQ)-25, a dry eye questionnaire, from baseline to day 28. The second primary outcome measure was the mean area change of corneal epithelial healing following the CXL procedure. The secondary outcome measures for this study were the eye dryness score (EDS), degree of fluorescein staining and supplemental artificial tear usage. Results Twelve subjects were enrolled in the study group and eight in the control group. At day 28, the NEI-VFQ-25 questionnaire demonstrated an improvement from baseline in the study group and a reduction in the control group, but the between-group comparison was not statistically significant (p > 0.05). There was a directional trend toward faster mean change of epithelial healing in the study group, but the difference was not statistically significant at any time point. There were four total adverse events, all of which were mild in nature and resolved without sequelae. Conclusions VNS is an attractive treatment option for patients following CXL. Patients hoping to avoid punctal occlusion or additional use of topical medications following a procedure such as CXL may be well suited for a neurostimulator treatment option like VNS that spares the ocular surface. Trial Registration Registered with clinicaltrials.gov (NCT05136924).